Anne of Green Gables : an illustrated classic - Montgomery, L. M. (Lucy Maud), 1874-1942 (Phnom Penh : Footprints International School, 2024)
Anne, an eleven-year-old orphan, is sent by mistake to live with a lonely, middle-aged brother and sister on a Prince Edward Island farm and proceeds to make an indelible impression on everyone around her.
Keywords: Orphans -- Fiction; Friendship -- Fiction; Islands -- Fiction; Country life -- Prince Edward Island -- Fiction; Prince Edward Island -- History -- 20th century -- Fiction; Canada -- History -- 1867-1914 -- Fiction